Ten apples up on top! - LeSieg, Theo., 1904-1991.; McKie, Roy (New York : Beginner Books, 1989)
A lion, a dog, and a tiger balance apples on their heads.
"Copyright renewed 1989"--t.p. verso.
Yellow price sticker on cover.
"75 word vocabulary"--Cover.
Published simultaneouly in Toronto, Canada by Random House of Canada Ltd.
Keywords: Stories in rhyme; Animals -- Juvenile fiction; Counting -- Juvenile literature